1986
DOI: 10.1620/tjem.149.133
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A transport in plasma of diabetic patients.

Abstract: The effects of diabetes on the vitamin A metabolism were studied. The concentrations of plasma retinol and retinyl ester were measured in diabetic patients using high-performance liquid chromatography (HPLC). In diabetic patients, the mean level of retinyl ester was significantly elevated compared to that of normal subjects (diabetes, 68.3+42.5 IU/100 ml of plasma ; study I, 87.6+64.3 IU/100 ml of plasma ; study II vs. normal, 29.8+ 10.3 IU/100 ml of plasma). The ultracentrifugal and column chromatographic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…These results are in agreement with earlier studies on humans or rats [1][2][3][4][5][6][7]. The increased liver concentrations of vitamin A may be explained in part by the increased food intake by the diabetic animals (>50%), since it has been shown that the hepatic storage of vitamin A is proportional to its intake [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in agreement with earlier studies on humans or rats [1][2][3][4][5][6][7]. The increased liver concentrations of vitamin A may be explained in part by the increased food intake by the diabetic animals (>50%), since it has been shown that the hepatic storage of vitamin A is proportional to its intake [25].…”
Section: Discussionsupporting
confidence: 92%
“…It has further been shown that diabetic patients not only have reduced plasma retinol but also elevated levels of retinyl esters [4], reflecting an increased hepatic storage [5]. Streptozotocin (STZ)-induced diabetic rats have decreased plasma retinol levels that are accompanied by an elevated hepatic concentration of vitamin A [6].…”
mentioning
confidence: 99%
“…Several studies have reported that serum levels of both carotene and vitamin A are within normal range in diabetes mellitus (Murrill et al, 1941;Kimble et al, 1946;Ramachandran, 1973). Recently, an increase in plasma retinyl esters has been reported in Type 2 diabetes (Wako et al, 1986) and a decrease in serum concentration of vitamin A and RBP in Type 1 diabetes (Basu et al, 1989). Other investigators found that retinol concentrations were signi®cantly decreased in Type 1 (Krempf et al, 1991) and increased in Type 2 diabetes mellitus as compared to control subjects (Krempf et al, 1991;Havivi et al, 1991;Sasaki et al, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Lower serum concentrations of retinol in patients with insulin-dependent diabetes (IDDM) and in streptozotocin-induced diabetic rats, in which the transport mechanism of retinol from liver to the target site is considered to be impaired, were reported. [1][2][3][4][5] In contrast, patients with non insulin-dependent diabetes (NIDDM) have greater serum retinol concentrations than normal subjects. [6][7][8] Recently, PPARg, a ligand-activated transcription factor and a member of the nuclear hormone receptor superfamily, was found to play a pivotal role in the expression of genes associated with metabolism and transport of glucose and lipids.…”
mentioning
confidence: 99%